Exploring Postgraduate Student’s Experiences on Values of Humanness During COVID-19: An Inquiry for Supportive Online Learning and Assessment - Cias Thapelo Tsotetsi; Masetshaba Agnes Tsosane (Interdisciplinary Journal of Education Research)
Previous research highlights significant disruptions to teaching and assessment time in universities due to strikes and the COVID-19 pandemic. The pandemic, which began in late 2019, forced institutions worldwide to close, prompting a shift to online teaching, learning, and assessment. In Africa, additional closures occurred due to student unrest. While the transition to online learning sought to maintain academic continuity, limited research exists on how postgraduate students experienced the values of humanness (botho) during this period. This qualitative study explores how postgraduate students perceived the values of botho in online learning and assessment during the lockdown. Fifty honours students participated in an assignment completed in groups of up to four, with 15 submissions received, including group and individual efforts. Students reflected on their experiences, highlighting positive outcomes such as knowledge sharing within groups. However, challenges emerged, including group members leaving unexpectedly due to non-cooperative peers, which left others to complete tasks individually with increased effort. The findings suggest that the principles of botho should be integrated into online assessment designs to address the challenges faced by students. Additionally, the study underscores the importance of bridging the digital divide to promote equitable online learning. Further research is needed to explore strategies that incorporate the values of botho while addressing technological and collaborative barriers in online education.